Young farmers and parents' perception for the future of agriculture: socio-spatial integration of Coffee Farmers in Jeneponto Regency. Issue 1 (March 2020) - Junais, I; Samsuar,; Daniel,; Ali, H M; Yusran,; Syarif, A; Mansyur, M H
Abstract: Farmer's social perception is an important factor in the future development of agriculture. Especially the perception of young farmers needs serious attention considering that they are the pioneers of agriculture in the future. This study aims to examine the perceptions of young farmers towards their future and parents' perceptions of the future of young farmers. The census study involved 151 coffee-farming families with productive-age children who were then interviewed separately. Data analysis using different test, factor analysis, then integrated in socio-spatial. The perception of the group of parents is greatly influenced by how they have strong access to farming, they assume that the activities of this sector require hard work, time consuming, energy and are synonymous with gross and dirty work. This is a precursor to form a social perception that more income is not the main benchmark in determining the social class of the community but rather the type of livelihood. The decision taken by farmer parents for their children is based more on social perceptions that farming work is still considered low in the social strata even though the income generated is in a decent category. In contrast to the perception of parents, young farmers are more optimistic about the future in developing business in agriculture seeing the potential and agricultural resources they have. The perception of young farmers is formed not entirely because of high education, but the ability to access information is a factor forming the perception of groups of young farmers, low education does not correlate with their ability to access information. Based on these results, we conclude that differences in perceptions are present as a result of differences in age backgrounds, perspectives, and characteristics. Poverty that has long ensnared the farming community has changed the social perception of the perspective of the current farming community, so that the perception emerged for farmers that leaving the agricultural sector is the best way to leave poverty. Therefore, it is necessary to launch an agricultural education system into the village, how the education system directly reaches the farming community in the village in order to create a modern agricultural social environment that is business-oriented in the community and family so that it can equate perceptions of the future agricultural business.